Solid‐Phase Parallel Synthesis of Functionalised Medium‐to‐Large Cyclic Peptidomimetics through Three‐Component Coupling Driven by Aziridine Aldehyde Dimers. Issue 25 (26th May 2015) - Treder, Adam P.; Hickey, Jennifer L.; Tremblay, Marie‐Claude J.; Zaretsky, Serge; Scully, Conor C. G.; Mancuso, John; Doucet, Annie; Yudin, Andrei K.; Marsault, Eric
Abstract The first solid‐phase parallel synthesis of macrocyclic peptides using three‐component coupling driven by aziridine aldehyde dimers is described. The method supports the synthesis of 9‐ to 18‐membered aziridine‐containing macrocycles, which are then functionalized by nucleophilic opening of the aziridine ring. This constitutes a robust approach for the rapid parallel synthesis of macrocyclic peptides.